A study of growth, development and carcass characteristics of the indigenous breeds of cattle in Northern Rhodesia - Black, J.G. (1956)
The growth, development and carcass characteristics of indigenous Angoni, Barotse and Tonga cattle in Zambia in comparison to European grade breeds were investigated. Discussions and data on live animal records, growth rate in body height and chest girth, body length, dressing percentage, percentage of hind quarters to fore quarters, meat to bone ratio on the dressed loin and carcass quality, as well as correlations of liveweight to body and carcass measurements included.